Effect Of Surface Roughness On Oil-Water Separation For Oil Skimmer - Hussin, Mohamed Saiful Firdaus; Ahmad, Mohd Nazri; Jumaidin, Ridhwan; Mohammad Taha, Mastura; Mansor, Muhd Ridzuan; Muhamad Damanhuri, Amir Abdullah; Mukhtar, Mohd Fariduddin; Wahid, Mohammad Khalid; Zakaria, Azrul Abidin (Asian Research Publishing Network (ARPN), 2021)
Uncontrolled production of fat, oil, & grease (FOG) in wastewater continues to increase each year as the number of restaurants increases. As wastes disposed directly into the drainage system, FOG may build up around the plumbing system of the wastewater system facility. Efficient development of the grease trap will reduce the impact of the problem and prevent the FOG contaminant in the sewage system. This research aimed to investigate the effect of surface roughness on oil skimming efficiency for the grease trap. Materials for oil skimmer were selected and characterized using water contact angle analysis, ImageJ software, scanning electron microscope (SEM), and profilometer. Materials were roughened by using 150 grid abrasive paper. It was found that roughness strongly influenced the wettability of the selected materials due to the air trap and its geometrical structure. The results revealed that acrylic skimmer is the most efficient compared to aluminium, paraffin, and polystyrene